1998
DOI: 10.1093/molehr/4.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of a novel pregnancy-associated soluble variant of the vascular endothelial growth factor receptor, Flt-1

Abstract: Angiogenesis is essential in physiological processes including ovulation, implantation and pregnancy. One of the most potent regulators is the cytokine vascular endothelial growth factor (VEGF). We provide evidence for a novel pregnancy-associated soluble variant of the VEGF receptor Flt-1. VEGF ranged from undetectable to 157.3 pg/ml (mean 49.9 pg/ml, SD 48.4 pg/ml) in plasma samples from normal volunteers (n = 10), but was undetectable in plasma from pregnant women (n = 12) and amniotic fluid (n = 10). Recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 64 publications
1
62
0
Order By: Relevance
“…free VEGF and free PlGF (22,23). We first confirmed that these ELISA kits measured only unbound VEGF or PlGF by performing a standard curve for VEGF and PlGF proteins in the presence of exogenous recombinant sFlt1.…”
Section: Figurementioning
confidence: 73%
See 1 more Smart Citation
“…free VEGF and free PlGF (22,23). We first confirmed that these ELISA kits measured only unbound VEGF or PlGF by performing a standard curve for VEGF and PlGF proteins in the presence of exogenous recombinant sFlt1.…”
Section: Figurementioning
confidence: 73%
“…Several authors have reported increased systemic VEGF levels in women with preeclampsia (31-34) while other authors have reported decreased levels (35-37), as we report here (Figure 2c). In reviewing the methodology of these studies carefully, we found that all studies reporting decreased VEGF (35-37) used a commercially available ELISA kit (R&D Systems), which, in fact, measures free (unbound) VEGF as previously shown by others (22,23,38). All studies reporting increased VEGF in preeclampsia used either radioimmunoassay or a non-R&D ELISA system, measuring total (bound and unbound) VEGF (31)(32)(33)(34).…”
Section: Figurementioning
confidence: 94%
“…The effects on NF-B activation on angiogenesis in the placenta are not well understood. HIF-1␣, VEGF, VEGF receptors, and TIE-2 have been detected on trophoblasts and endothelial cells (22,(37)(38)(39). The mRNA levels of VEGF and VEGF receptors were dependent on gestational age and mode of delivery, but no analysis of chorioamnionitis was included (38).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, after incubation with rabbit anti-human NF-B, an HRP-conjugated goat-anti-rabbit Capillaries that were stained along the circumference were recorded as positive. VEGF, VEGF-R1, VEGF-R2, TIE-2, and HIF-1␣ were expressed on all endothelial cells (22,(37)(38)(39). Therefore, the intensity of staining was measured with a three-step semiquantitative scale (magnification ϫ200) as weak (ϩ1), moderate (ϩ2), or strong (ϩ3) (40)…”
Section: Methodsmentioning
confidence: 99%
“…In fact, at least part of the dilator response to VEGF has been ascribed to induction of nitric oxide (NO) release (10). Of interest, a soluble form of VEGFR1 also exists; it is secreted by endothelial cells and was shown to inhibit VEGF activity in vitro by sequestering the ligand (1,(11)(12)(13).…”
mentioning
confidence: 99%